Prognostic significance of different congestion evaluation modalities in acute heart failure patients classified according to left ventricular ejection fraction. (14th October 2021) - Palazzuoli, A; Ruocco, G; Gargani, L; Coiro, S; Ambrosio, G; Girerd, N
Abstract: Background: Congestion is the main reason for hospital admission in patients with acute heart failure (AHF). Lung ultrasound (LUS) examination has been proposed as a simple, accurate, and available tool to assess pulmonary congestion, adding significant prognostic insights to clinical examination. Aim: This is a multicentre retrospective study aiming to investigate the prognostic value accuracy of B-lines, compared with B-type natriuretic peptide (BNP) and clinical congestion both at admission and at discharge in a large cohort of patients admitted for AHF divided according to ejection fraction cut-off in HFrEF, HFmrEF and HFpEF). Methods: We analysed the merged data of four cohorts hospitalized for AHF. All patients underwent clinical assessment, echocardiography evaluation, BNP measurement and LUS measurements in 8 or 28 chest zones. The primary outcome was the composite endpoint of all-cause mortality and/or HF re-hospitalization at 60 and 180 days. Results: A total of 551 patients (264HFrEF, 100 HFmrEF and 187 HFpEF) were included. Median age was 77 [69–82] and 337 patients were men. Dividing our population according to HF classifications, we found that admission BNP levels were significantly higher in HFrEF compared to HFmrEF and HFpEF (p=0.002). No significant differences in terms of admission B-lines count were found among groups (p=0.80). ROC Curve analysis showed the significant prognostic power (p<0.05) of clinical congestion score, BNP and B-lines at admission. These findings were confirmed also for the same variables at discharge (p<0.05). Univariate analysis confirmed as predictor of poor prognosis admission congestion score≥2 (HR: 4.12 [2.84–5.99]; p<0.001), admission B-lines>30 (HR: 1.43 [1.02–1.99]; p=0.035), tricuspid anular plane systolic excursion (TAPSE) ≤16 mm (HR: 1.74 [1.25–2.42]; p=0.001), inferior cave vein (ICV) >21 mm (HR: 2.74 [1.80–4.18]; p<0.001) and E/e' ≥15 (HR: 1.71 [1.18–2.47]; p=0.005). Multivariable analysis demonstrated that admission B-lines were significantly related to poor prognosis only in HFrEF (p=0.025) and HFpEF (p=0.041), but not in HFmrEF (p=0.59). Considering the change from admission to discharge of congestion score, BNP and B-lines, the Δ B-lines during hospitalization remains the only significant predictor of poor prognosis (≥60days) across HF spectrum (HFrEF, HFmrEF and HFpEF; p≤0.001). Conclusions: Although both clinical congestion signs and B-lines were predictors of all-cause mortality and HF rehospitalization at 180 days, the changes of these variables during hospitalization were the stronger predictor of poor outcome. In particular, an inadequate B-lines in-hospital reduction (Δ B-lines <9), was significant associated to increased risk for adverse event in all HF subtypes. Current study confirm the relevance to apply a multiparametric congestion assessment in order to better stratify hospitalized AHF patients. Funding Acknowledgement: Type of funding sources: None.